2018
DOI: 10.5812/iranjradiol.57231
|View full text |Cite
|
Sign up to set email alerts
|

Contributory Factors to Hemorrhage After Ultrasound-Guided Fine Needle Aspiration of Thyroid Nodules with an Emphasis on Patients Taking Antithrombotic or Anticoagulant Medications

Abstract: Background: Thyroid nodules are a common clinical problem and ultrasound-guided fine needle aspiration (US-FNA) biopsy is widely used for evaluation of thyroid nodules. However, few studies have addressed the contributing factors to hemorrhage after US-FNA of thyroid nodules. Objectives: To assess the contributory factors related to patient characteristics, ultrasound (US) features of the thyroid nodules, and the US-FNA procedures to affect hemorrhage complications after US-FNA of thyroid nodules. Methods: Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Ultrasound-guided FNA of thyroid nodules is a simple, minimally invasive, and safe test generally performed in ambulatory care [1,8]. The most common complications are local pain or discomfort and mild hematoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided FNA of thyroid nodules is a simple, minimally invasive, and safe test generally performed in ambulatory care [1,8]. The most common complications are local pain or discomfort and mild hematoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was kept under close surveillance and the hematoma was monitored by imaging tests (CT). However, given the unfavorable evolution with its persistence and compressive effect on the trachea, surgical drainage was necessary [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of factors such as hemorrhagic disorders, anticoagulant/anti-platelet drugs, and hypertension increases the susceptibility to hemorrhagic complications [ 4 , 6 ]. The risk is also increased in the presence of a hypervascularized gland, nodules composed of numerous aberrant vessels with relatively thin walls, and intra-nodular arteriovenous derivations [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant antithrombotic drugs should be discontinued 3-10 days before FNAB, due to the increased risk of hemorrhagic complications. [18] It has been reported that on-site evaluation of the FNAB specimens by a cytopathologist decrease the biopsy repetition rates and false-negative results and increase the biopsy success. [4,19] Stacul et al found that on-site cytopathological evaluation reduced the diagnostic failure rates from 14% to 4%.…”
Section: Discussionmentioning
confidence: 99%